KERJASAMA INTERNASIONAL DALAM MENGEMBANGKAN KEBIJAKAN YANG EFEKTIF UNTUK MENANGANI MASALAH NARKOTIKA DI INDONESIA - Nainggolan, Richard Marolop (Fakultas Hukum Universitas Kristen Indonesia, 2024)
International cooperation is essential in designing effective regulations and policies to deal with the narcotics problem in Indonesia. This article was written to explain how to handle narcotics problems in Indonesia through international cooperation in narcotics law. This article also aims to explore the concept of international cooperation policy in efforts to prevent and eradicate narcotics, both in terms of reducing demand and reducing supply. A nation's position in the international system, typically defined by its material power, determines the scope and goals of its foreign policy. In this article, we discuss the concept of international cooperation in developing effective policies to deal with the narcotics problem in Indonesia. This research uses normative legal research methods and qualitative empirical research in the form of evaluative research to analyze applicable positive law. The conclusion is that Indonesia must participate in open international dialogue to overcome the narcotics problem in Indonesia. Apart from that, Indonesia also needs to strengthen cooperation with other countries and increase collaboration in law enforcement. There is a need for government representatives who are specifically tasked with dealing with narcotics problems to reduce bureaucracy that hampers cooperation between countries and accelerates joint efforts in combating cross-border narcotics trafficking.